The Effectiveness of Technology, Pedagogy and Content Knowledge (TPACK) in Learning - Nalurita Absari; Priyanto Priyanto; Muslikhin Muslikhin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
The study examined the factors affected teachers' Technology, Pedagogy and Content Knowledge (TPACK). Those factors are Technology Knowledge (TK), Pedagogy Knowledge (PK), Content Knowledge (CK) and Technology Pedagogy Knowledge (TPK). Curriculum 2013 has been applying for 5 years. However, an evaluation of how does the teacher deliver learning subjects (pedagogy knowledge), and the implementation of subject mastery (content knowledge) and technology mastery (technology knowledge) is strongly suggested. The study was quantitative with an associative method involving 200 teachers in Salatiga region as samples drawn with simple random sampling. The results of the study showed that PK has a positive effect on TPACK, while TK and CK do not have a positive effect on TPACK. Furthermore, TK, TPK, PK have positive effects on TPK, and TPK has a positive effect on TPACK. This study also suggested that age influences the development of technological knowledge and if one of the knowledge is not possessed by a teacher, the learning process will achieve maximum outcomes.